(i²/1)= (1/i²)

√(i²)/√1= (√1)/(√i²)

Normally, in such paradoxes, this is where the mistake lies.

Since a² = b²,

it cannot be inferred that a=b.

Taking square root on both sides of an equation should always have the

'±' sign, after the square root is worked out.

I suspect it is this curious phenomenon:

(-1)² = 1²

-1 = 1 ...?

Making:

√(i²)/√1= (√1)/(√i²)

i/1 = 1/i ...?

Because:

1/i = (1 x i) / (i x i) = i/i² = i / -1 = -i

* basks in glow of very rare victory, hoping it lasts *

]]>(-1/1)= (1/-1)

(i²/1)= (1/i²)

√(i²)/√1= (√1)/(√i²)

i/1= 1/i

i²= 1 (cross-multiplication)

Contradiction!!

How to solve this paradox?

I also don't know the answer.